In Covers Green and Gold: Fin-de-siècle Evelina - Kochkina, Svetlana (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2023)
The first novel by Frances Burney, Evelina, Or, a Young Lady’s Entrance into the World, published in 1778, has enjoyed long-standing popularity, having never gone out of print in English. A distinct cluster of its editions appeared at the end of the 19th - beginning of the 20th century. This period in book history was marked by the creative work of private-press book designers, printers, binders, and illustrators inspired by the Aestheticism, Arts and Crafts, and Art Nouveau movements. Even though their pioneering work was destined for narrow circles of collectors and connoisseurs, it profoundly influenced the development of both industrial and artists’ book design, heightening the awareness of books’ aesthetic appeal. The fin de siècle was a time of nostalgia for idealized pre-industrial society, symptomatic of Victorian and Edwardian escapism, which found its expression in lavish book ornaments and illustrations executed in the Directoire and Louis XVI styles. Late 19th - early 20th-century Evelinas, illustrated and decorated by Aubrey Beardsley, Arthur Rackham, and Hugh Thomson, produced by Dent, Newnes, and Macmillan, reflect a profound influence that innovative private presses had on general publishing practices and the quality of industrially produced books. These Evelinas, beautifully illustrated, bound in decorative covers, and well-printed, exemplify both the newly awakened interest in the book’s physical make-up and aesthetical aspects and the late-Victorian and Edwardian escapist nostalgia characteristic of fin de siècle publishing.